Efektifitas Kebijakan Makroprudensial dalam Mengatasi Credit Boom, Asset Bubbles dan Prosiklikalitas Modal: Analisis Meta - Naufal Putra Kusuma (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
Crises most often occur due to the procyclicality of asset prices, bank credit, and foreign capital flows. The existence of macroprudential policies is expected to mitigate the occurrence of a crisis. This literature review discusses macroprudential policy instruments that can mitigate the procyclicality of credit booms, asset bubbles, and the procyclicality of capital flows in developing countries. Using metaanalysis, we reviewed the five works of literature for each procyclicality. The results show that LTV is the most frequently chosen instrument and is effective in mitigating the three risks of procyclicality. CCB instruments can mitigate credit booms, and DTI can withstand asset price spikes. In addition, the reserve requirements and capital requirements instruments are considered effective in overcoming the procyclicality of capital flows. It can be concluded that the policy is the right choice for mitigating a crisis.